The Haematological Profile of Patients of Pulmonary - Padhariya, Jitendra Dhanjibhai; Shah, Shaila N (Annals of Pathology and Laboratory Medicine, 2019)
Background: Tuberculosis is a major public health problem in India having variety of hematological manifestations. Though tuberculosis is a common condition, there is a paucity of literature in the hematological changes associated with tuberculosis. Study done to evaluate the presence, extent and severity of haematological abnormalities in Pulmonary Tuberculosis. Methods: One hundred patients of fresh pulmonary tuberculosis with sputum positive for acid fast bacilli (AFB) were included and AIDS patients, disseminated tuberculosis and patients receiving ATT drugs were excluded in this study. The various hematological parameters were studied by means of hemogram by automated cell counter and peripheral smear examination. Result: Anemia was seen in 88% of patients. In spite of the infection, 51 patients had a normal leukocyte count. Leucocytosis as a response to infection was observed in 46 patients. Three patients had leucopenia. Thrombocytosis was observed in 17 patients while thrombocytopenia was observed in 4 patients. 99% patients had increased erythrocyte sedimentation rate (ESR). Conclusion: Variety of hematological abnormalities has been demonstrated in patients with pulmonary tuberculosis in the present study. The degree of anemia is directly proportional to the severity of tuberculosis and severe anemia in turn increases the morbidity and the mortality in tuberculosis. Patients infected with TB should be monitored haematologically.